Piperlongumine alleviates corneal allograft rejection via suppressing angiogenesis and inflammation - Fan, Xiangyu; Qiu, Jini; Yuan, Tianjie; Zhang, Jing; Xu, Jianjiang (Frontiers in Immunology, 2022)
Background. Neovascularization and inflammatory response are two essential features of corneal allograft rejection. Here, we investigated the impact of Piperlongumine (PL) on alleviating corneal allograft rejection, primarily focusing on pathological angiogenesis and inflammation. Methods. A murine corneal allograft transplantation model was utilized to investigate the role of PL in preventing corneal allograft rejection. PL (10 mg/kg) or vehicle was intraperitoneally injected daily into BALB/c recipients from day -3 to day 14. The clinical signs of the corneal grafts were monitored for 30 days. Corneal neovascularization and inflammatory cell infiltration were detected by immunofluorescence staining and immunohistochemistry. The proportion of CD4+ T cells and macrophages in the draining lymph nodes (DLNs) was examined by flow cytometry. In vitro, HUVECs were cultured under hypoxia or incubated with TNF-α to mimic the hypoxic and inflammatory microenvironment favoring neovascularization in corneal allograft rejection. Multiple angiogenic processes including proliferation, migration, invasion and tube formation of HUVECs in hypoxia with or without PL treatment were routinely evaluated. The influence of PL treatment on TNF-α-induced pro-inflammation in HUVECs was investigated by real-time PCR and ELISA. Results. In vivo, PL treatment effectively attenuated corneal allograft rejection, paralleled by coincident suppression of neovascularization and alleviation of inflammatory response. In vitro, PL distinctively inhibited hypoxia-induced angiogenic processes in HUVECs. Two key players in hypoxia-induced angiogenesis, HIF-1α and VEGF-A were significantly suppressed by PL treatment. Also, TNF-α-induced pro-inflammation in HUVECs was hampered by PL treatment, along with a pronounced reduction in ICAM-1, VCAM-1, CCL2, and CXCL5 expression. Conclusions. The current study demonstrated that PL could exhibit both anti-angiogenic and anti-inflammatory effects in preventing corneal allograft rejection, highlighting the potential therapeutic applications of PL in clinical strategy.